G130 Tackling the childhood obesity crisis – are acute paediatricians playing their part?. (24th May 2017) - Harvey, K; McDermott, H; Coles, W; Elliott, S; Anandaram, A; Ismail, S; McMullan, N; Webb, E; Kirk, J
Abstract : Background: Childhood obesity is the most grave health issue facing children today, with half of 10 year olds predicted to be affected by 2020 (RCPCH). Acute paediatricians have a duty to identify and manage childhood obesity, as they would other comorbid conditions. Many paediatricians are, however, reluctant to broach this subject with parents in the acute setting; while parents state that they would want to be told if their child was found to be overweight while in hospital. Identification of obesity also impacts on medical management, such as prescription of various drugs based on ideal body weight. Aims and Objectives: To establish whether overweight children are correctly identified and managed in Children's Assessment Units (CAU). Methods: We examined the records of all children aged >2 years attending five regional CAUs over 72 hours. Data were collected including height, weight and BMI. A quality improvement package (QIP) was then introduced, consisting of an educational presentation to the medical team, and educational posters in CAU. Re-audit was performed in three of the centres at least 3 weeks later. Results: One hundred and thirty one children were included in the initial study. Weight was recorded in 115 (87%, range 65%– 100%). Height was recorded in 45 (34%, range 0%–80%). BMI was calculated in 0/131; obesity was documented as present in one case although no action was taken. Using height and weight data we were able to calculate BMI centiles in 44 (34%) children; of these 14 (32%) had a BMI above the 91st centile. Following the QIP there was no improvement in obesity detection, with weight obtained in 45/48 (93%), height obtained in 14/48 (29%) and obesity recognised in none of the children. Conclusions: Identification of obesity at CAU attendance is poor. There is large inter-centre variability in height and weight documentation; all centres are, however, universally poor at identifying obesity. Simple educational interventions were ineffective at improving this. With childhood obesity representing a significant and serious paediatric health issue, we must seek other ways to improve identification as a matter of priority.